DEVELOPING SCHOOL STUDENTS’ CREATIVE THINKING THROUGH HISTORICAL ART AND LANDSCAPE PAINTING - Rustamova Farangiz Asqarbek qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines strategies for enhancing creative thinking in school students by using historical art and landscape painting. It explores pedagogical methods that integrate visual arts into classroom instruction to develop students’ imagination, analytical skills, and aesthetic understanding. Historical landscapes provide a context for interpreting historical events, stimulating visual perception, and fostering independent artistic expression. The study highlights how teachers can utilize these artworks to engage students in creative problem-solving, visual storytelling, and historical reflection. Findings indicate that historical art significantly improves students’ ability to think critically, express ideas artistically, and appreciate cultural heritage.